Integrating Green Economy Concepts to Support the Achievement of SDGs Tenganan Dauh Tukad Village, Manggis District, Karangasem Regency - JAYAWARSA, A. A. Ketut; NARINDRA, A. A. Ngurah Mayun; SAPUTRA, Komang Adi Kurniawan (Indonesia Strategic Sustainability, 2024)
The implementation of the Green Economy in MSMEs in Karangasem, Bali, highlights dedication to sustainable development and environmental preservation. Many MSMEs in the region adhere to environmentally friendly practices, such as the use of sustainable materials and technology. In the tourism sector, for example, the business world focuses on environmentally friendly tourism with effective waste management and the use of renewable energy. Likewise, agricultural MSMEs are turning to organic methods to minimize the use of harmful chemicals. Government training and mentoring programs support these environmentally friendly practices. In Tenganan Village, the Ata craftsmen group exemplifies this approach. Known for their expertise with the roots of the Ata plant, the artisans uphold traditional methods while adapting to modern trends. Although the production process is environmentally friendly, the Ata tree trunks used as raw materials cannot be cultivated, and greater awareness of Green Economy principles is needed among partners.The service team is committed to educating these craftsmen about Green Economy practices to increase productivity and economic sustainability. In addition, although craftsmen currently use simple ledgers for financial recording, they lack detailed cost accounting for raw materials and operations. Introducing financial reporting that is aligned with Green Economy principles will improve accountability and financial management. With the existence of 15 independent Ata craft groups in Tenganan Village, the establishment of an integrated supervisory body can further support the integration of Green Economy practices and overall business efficiency.